To simplify the expressions given, let's evaluate each one step by step.
-
For \((-2)^{-8} \cdot (2)^{11}\): \[ (-2)^{-8} = \frac{1}{(-2)^8} = \frac{1}{256} \] \[ (2)^{11} = 2048 \] Thus, \[ (-2)^{-8} \cdot (2)^{11} = \frac{1}{256} \cdot 2048 = \frac{2048}{256} = 8 \]
-
For \(\left(\frac{1}{2}\right)^{-3}\): \[ \left(\frac{1}{2}\right)^{-3} = 2^3 = 8 \]
-
For \(2^6 - \frac{2^4}{2^2}\): \[ 2^6 = 64, \] \[ \frac{2^4}{2^2} = 2^{4-2} = 2^2 = 4 \] Thus, \[ 2^6 - \frac{2^4}{2^2} = 64 - 4 = 60 \]
-
For \(\frac{1}{4^{-2}}\): \[ 4^{-2} = \frac{1}{4^2} = \frac{1}{16} \] So, \[ \frac{1}{4^{-2}} = 16 \]
Now we have the simplified values:
- \((-2)^{-8} \cdot (2)^{11} = 8\)
- \(\left(\frac{1}{2}\right)^{-3} = 8\)
- \(2^6 - \frac{2^4}{2^2} = 60\)
- \(\frac{1}{4^{-2}} = 16\)
Putting these values in order from least to greatest:
- 60
- 16
- 8
- 8
So, if we order everything from least to greatest:
- \(60\)
- \(16\)
- \(8\)
- \(8\)
The final order from least to greatest is:
- \(60\)
- \(16\)
- \(8\)
- \(8\) (but both are the same, so they can be grouped)
Thus, the final presentation would be:
- \(60\)
- \(16\)
- \(8\) (doubled)
If you need them uniquely, \(60 < 16 < 8\).